2013
DOI: 10.1136/bjophthalmol-2013-303434
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of and attitudes to genetic testing for inherited retinal disease: a patient perspective

Abstract: Background/aimsThe views of people with inherited retinal disease are important to help develop health policy and plan services. This study aimed to record levels of understanding of and attitudes to genetic testing for inherited retinal disease, and views on the availability of testing.MethodsTelephone questionnaires comprising quantitative and qualitative items were completed with adults with inherited retinal disease. Participants were recruited via postal invitation (response rate 48%), approach at clinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 21 publications
4
31
0
1
Order By: Relevance
“…Retinitis pigmentosa was the most common diagnosis in the present sample (42%), matching its position as the most common inherited retinal condition. 20,21 Finally, the sample was a purposive one, drawn from a wider study; 10 this means that although participants were deliberately selected to gather a range of views, further research is necessary to assess whether such views are held more widely; the use of a control group in the study would be useful for this purpose. Our participants may be more invested in obtaining genetic information than the general public, and hence our results are expected to overestimate interest in and willingness to pay for genetic testing in the context of inherited retinal disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinitis pigmentosa was the most common diagnosis in the present sample (42%), matching its position as the most common inherited retinal condition. 20,21 Finally, the sample was a purposive one, drawn from a wider study; 10 this means that although participants were deliberately selected to gather a range of views, further research is necessary to assess whether such views are held more widely; the use of a control group in the study would be useful for this purpose. Our participants may be more invested in obtaining genetic information than the general public, and hence our results are expected to overestimate interest in and willingness to pay for genetic testing in the context of inherited retinal disease.…”
Section: Discussionmentioning
confidence: 99%
“…The available evidence suggests that patients are generally enthusiastic towards testing and feel that it should be available, even if they may choose not to utilise it themselves. [8][9][10][11] Recently, Eden et al 4 examined the monetary value that individuals with and without prior experience of retinitis pigmentosa placed upon genetic counselling and testing. Responding to a hypothetical scenario, the majority of their sample reported that they would seek genetic counselling and testing.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Telephone questionnaires with the larger group of participants identified that a self-reported understanding was greater in those with higher educational achievement, suggesting that the need for information is greater in those with lower educational achievement or that they are less confident. 7 Access to information may also be more difficult for those with lower educational achievement. The findings suggest that either or both of the initial provision or the recall of information may have been poor.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment to the larger, telephone questionnaire has been described elsewhere. 7 Face-to-face interviews were conducted with the 50 participants using a semistructured interview guide. Interviews were recorded, transcribed verbatim, analysed and coded by two researchers using a thematic approach.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation